Inter-relationship between the housing market and housing finance system: evidence from Malaysia - Said, Rosli; Adair, Alaistair; McGreal, Stanley; Majid, Rohayu (International Journal of Strategic Property Management, 2014)
The Malaysian housing market and associated housing finance system have expanded significantly as a result of rapid urbanisation since the late 1980s. The key aspect of this paper is to analyse the inter-relationship between the housing market and housing finance system in Malaysia. The paper employs Vector Autoregressive approach and Granger Causality test to empirically investigate this inter-relationship. In Malaysia, no housing studies has actually looked into or used this approach to identify the inter-relationship between these two elements. The key findings show that there is a strong inter-relationship between the housing market and housing finance system. The direction of causality shows that there is a bi-directional relationship between the housing market and housing finance system. These inter-relationships provide evidence that sound performance of the sub-markets within the housing finance system is a determinant prerequisite of the robustness of the housing finance system, if a healthy performance of the housing market is to be achieved.First Publish Online: 20 Jun 2014